SWOT Analysis for Enhancing the Competitiveness of Gambung Cake SMEs in Luwu Regency, Indonesia - Ruslan Mahfuddin; Muhammad Haekal Yunus; N. Nasruddin (Golden Ratio of Mapping Idea and Literature Format, 2026)
This study aims to analyze the internal and external factors affecting the competitiveness of Gambung Cake Small and Medium-Sized Enterprises (SMEs) in Luwu Regency and formulate strategies for enhancing their competitiveness through a SWOT analysis approach. Gambung Cake is a traditional local culinary product with significant economic potential; however, it faces various challenges in an increasingly competitive market environment. This research employed a qualitative descriptive method, with data collected through direct observation, in-depth interviews with SME owners, and documentary studies. Data were analyzed using the SWOT matrix to identify strengths, weaknesses, opportunities, and threats, as well as the Internal-External (IE) matrix and SWOT matrix to formulate strategic alternatives. The findings indicate that Gambung Cake SMEs possess notable strengths in terms of product uniqueness and distinctive local tastes. However, they face weaknesses related to marketing, management, and limited capital. Opportunities include the growing interest of tourists in local culinary products and support from local government initiatives, whereas the primary threats stem from competition with similar products and changing consumer preferences. The recommended strategies include strength–opportunity (SO) strategies to maximize the unique characteristics of the product in targeting tourism markets; weakness–opportunity (WO) strategies to improve human resource capacity and access to financing; strength–threat (ST) strategies to maintain product advantages amid increasing competition; and weakness–threat (WT) strategies to minimize internal weaknesses in responding to external threats. This study is expected to contribute to the development of Gambung Cake SMEs by helping business owners better understand their business conditions, formulate effective marketing strategies, enhance competitiveness, and plan business development more systematically in the Luwu Regency. The SWOT analysis results indicate that Gambung Cake SMEs are currently in a growth phase, supporting the implementation of aggressive growth strategies (Supporting Aggressive Strategies).